Skin infections diagnosis and treatment - Hall, Brian J. 1981-; Hall, John C. 1947- (Cambridge University Press, 2009)
This is the first textbook linking the two disciplines of dermatology and infectious diseases. As the number of elderly, AIDS, transplant and cancer surviving patients continues to rapidly increase worldwide, all medical personnel need to be able to rapidly recognize and treat infections. The skin is the most easily accessed and monitored of all organs and is often the first sign of infection. Knowledge of the integument's link to infection is a must for the modern medical nurse, nurse practitioner, medical student, resident and practitioner. To accomplish these goals, the text features authors from around the world who are considered experts in their various fields of expertise. The book is organized into types of infections, locations in the integument, and specific subpopulations of patients at risk and regional variations of infections.